Cooperative-VBO model for polymer/graphene nanocomposites - Acar, A.; Colak, O.; Correia, J. P. M.; Ahzi, S. (ELSEVIER SCIENCE BV, 2018)
The Cooperative Viscoplasticity theory based on overstress (VBO) theory which is initially developed for polymers is modified to model the mechanical behavior of graphene-polymer nanocomposites. The modifications are proposed for both the elastic and viscoplastic deformation. For the elastic contribution, an effective modulus definition which covers the agglomeration effects is implemented into the Cooperative-VBO theory. A strain rate, temperature, graphene volume fraction and agglomeration rate dependent elasticity modulus is obtained. In order to model the visco-plastic deformation, two scalar material parameters, activation energy and activation volume are defined as functions of graphene volume ratio using Takayanagi averaging approach. The newly defined graphene volume fraction, agglomeration rate, temperature and strain rate dependent elasticity modulus and activation energy and free volume for nanocomposites are incorporated into the Cooperative-VBO model. In this manner, a constitutive model which covers the total viscoelastic-viscoplastic deformation of graphene-polymer nanocomposites is developed. The capabilities of the introduced model are demonstrated by predicting uniaxial compression behavior of pristine epoxy and different graphene content nanocomposites. In addition, storage modulus obtained from a Dynamic Mechanical Analysis (DMA) are compared with predicted values for neat epoxy, 0.1 wt% and 0.5 wt% graphene-epoxy nanocomposite. The simulation results are compared to experimental data from the literature. A fair agreement with experimental data is obtained.
Keywords: Polymer; Epoxy; Graphene; Nanocomposite; Modeling; Cooperative-VBO; Elastic-viscoplastic deformation; GRAPHENE-EPOXY NANOCOMPOSITES; CLOSED-FORM SOLUTIONS; MECHANICAL-PROPERTIES; AMORPHOUS POLYMERS; TRANSITION-TEMPERATURES; DEFORMATION-BEHAVIOR; MONOLAYER GRAPHENE; ELASTIC PROPERTIES; FINITE-ELEMENT; STRAIN RATES; Materials Science; Mechanics